2022
DOI: 10.1371/journal.pone.0262192
|View full text |Cite
|
Sign up to set email alerts
|

The social specificities of hostility toward vaccination against Covid-19 in France

Abstract: Equal Access to the COVID-19 vaccine for all remains a major public health issue. The current study compared the prevalence of vaccination reluctance in general and COVID-19 vaccine hesitancy and social and health factors associated with intentions to receive the vaccine. A random socio-epidemiological population-based survey was conducted in France in November 2020, in which 85,855 adults participants were included in this study. We used logistic regressions to study being "not at all in favor" to vaccination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
2
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
4
25
2
3
Order By: Relevance
“…[7] This could relate to the fact that members of the working classes have a perception of their body and their health that is more distant from medical diagnoses and recommendations than the upper class. [33] Racialised minorities, who had greater reluctance towards receiving a Covid-19 vaccine in France and in many countries[13,31] also appeared to be less likely to be vaccinated, as found in British and US surveys. [6,8,20,34] Numerous studies have shown that racialised minorities[24,35] have less confidence in the healthcare system and in caregivers than the mainstream population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] This could relate to the fact that members of the working classes have a perception of their body and their health that is more distant from medical diagnoses and recommendations than the upper class. [33] Racialised minorities, who had greater reluctance towards receiving a Covid-19 vaccine in France and in many countries[13,31] also appeared to be less likely to be vaccinated, as found in British and US surveys. [6,8,20,34] Numerous studies have shown that racialised minorities[24,35] have less confidence in the healthcare system and in caregivers than the mainstream population.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it is interesting to note that social differences in vaccination practices overlapped with the social distribution of vaccine reluctance observed in France eight months earlier, except for gender differences. [13] Indeed, women were no less likely to be vaccinated than men, although they were more reluctant to get vaccinated in France, as in many countries, before the vaccine was made available to all. [31] Faced with the reality/possibility of prevention, it is as if their gendered reflexes as guardians of the family's health came into play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a context where governments and scientists have taken the lead in managing the pandemic crisis, it is all the more important to analyse vaccination practices along with consideration of the trust that people place in the government (12)(13)(14)(15). Many studies have shown that COVID-19 vaccination intentions are related to trust in the government (11,(15)(16)(17)(18)(19)(20). One study, in the UK, simultaneously considered trust in the government and in scientists: COVID-19 hesitancy was associated with low trust in scientists and doctors but the correlation was weaker with trust in government (16).…”
Section: Introductionmentioning
confidence: 99%
“…In France, a new program of primary prevention interventions among HCS started in 2019, called "Service Sanitaire des Etudiants en Santé", and has been shown to improve misconceptions and hesitancy surrounding vaccines [25]. Our study showed that female students have better VC than male students, while Bajos et al highlighted a gendered reluctance toward vaccination in general (but even more so, regarding vaccination against COVID-19) [26]. This could be explained by better follow-up by a healthcare professional due to the prescription of a contraceptive method [27].…”
Section: Discussionmentioning
confidence: 56%